Técnicas especiais de investigação em relação aos crimes praticados por facções criminosas: infiltração, ação controlada e o confisco alargado - Uchôa, Romildson Farias (2024)
The dissertation deals with investigation, the preliminary phase of criminal prosecution, applied to criminal factions, regarding the application of special techniques of infiltration and controlled action, typical instruments for combating criminal organizations (Orcrim). Criminal investigative activity has a formal constitutional basis, as well as a finalistic or efficient one, resulting from the objective dimension of fundamental rights, which are anchored in articles 5, 6, 37 and 144 of the Constitution. In this context, there is a need to reconcile the duty of protection and efficiency in the provision of public security with the citizen’s individual guarantees. This results in a series of legal limitations to the aforementioned techniques, in addition to the physical and practical limits themselves, such as the risk to the lives of the undecover police officers and the ethical and legal limits of their actions in the context of societas sceleris. Such species of Orcrim constitute a typically Brazilian criminal arrangement, but with similar ones on an international level. Specifically, the research aims to propose changes not only to legislation, but also to methodologies and work strategies in the pursuit of the aforementioned organizations. For this, it is necessary to preliminarily analyze and describe the business model and organization of the factions. The present study is justified by the difficulties and obstacles, the deficient application of techniques and the need to respond to the growing insecurity and violence. Alongside the aforementioned tools, another one with great functionality appears, the extended confiscation, a type of asset constriction, enshrined in article 91-A of the Penal Code, still little used. Therefore, the hypothesis is sustained, which can serve both as a strategy and as a legal basis for the application of the techniques initially mentioned and, as a rule, limiting fundamental rights. The objectives of this study are, in general, to describe the way in which the techniques have been applied, together with the view of how the criminal factions have been investigated, which, a priori, has been carried out in a precarious way. The research was elaborated based on the hypothetical-deductive method, through the bibliographic and documentary review, and in certain situations, the inductive method was used, when studying cases, mainly through the analysis of judicial decisions and jurisprudence, and also the deductive. The conclusions are that: the persecution has not been directed directly at factions, but, in most cases, at members, nuclei or specific crimes of these groups, indicating a lack of standardized methodology; the establishment of investigations among the most different circumscriptions reveals rework or absence of investigations in many territorial bases where such groups are present; infiltration is little used, due to its intrinsic limitations and controlled action is used in generic terms, without police and judicial standardization. The techniques, combined with extended confiscation, can establish a feasible methodology, directing infiltration to activities in which the police officer does not need to commit violent material acts, nor urged to do so, since he will assume a logistical and/or professional launderer profile, creating an operational and legally controllable environment, which can prioritize the identification of assets and the consequent financial asphyxiation of groups and people of outstanding importance in criminal factions.